A Sink Node Allocation Scheme in Wireless Sensor Networks Using Suppression Particle Swarm Optimization - Nakano, Hidehiro; Yoshimura, Masaki; Utani, Akihide; Miyauchi, Arata; Yamamoto, Hisao (IntechOpen, 2010)
None